2005
DOI: 10.1556/avet.53.2005.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Study on the role of gastric Helicobacter infection in gross pathological and histological lesions of the stomach in finishing pigs

Abstract: The prevalence of gastric Helicobacter infection in finishing pigs and the influence of this infection on gastric lesions was studied. Stomachs of 89 finishing pigs from 27 randomly selected herds were sampled at the slaughterhouse. Forty cases (Group A) were selected based upon the presence of gross pathological lesions in the pars oesophagea, and further 49 cases were obtained at random (Group B). Three samples of gastric tissue (junction of pars oesophagea and pars cardiaca, fundic area, and pyloric area) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
1
11
0
4
Order By: Relevance
“…Some studies have found an association between these two events (Barbosa et al, 1995;Queiroz et al, 1996;Roosendaal et al, 2000;Choi et al, 2001), while others have not (Grasso et al, 1996;Krakowka et al, 1998;Melnichouk et al, 1999). Anyway, even if the presence of the microorganism is not strictly related to the ulcer development, it can play a role in the multifactorial aetiology of the disease (Szeredi et al, 2005).…”
mentioning
confidence: 99%
“…Some studies have found an association between these two events (Barbosa et al, 1995;Queiroz et al, 1996;Roosendaal et al, 2000;Choi et al, 2001), while others have not (Grasso et al, 1996;Krakowka et al, 1998;Melnichouk et al, 1999). Anyway, even if the presence of the microorganism is not strictly related to the ulcer development, it can play a role in the multifactorial aetiology of the disease (Szeredi et al, 2005).…”
mentioning
confidence: 99%
“…Esses resultados são concordantes com os encontrados por Szeredi et al (2005), que, por meio da IHQ, encontraram maior infecção na região cárdica, seguida da pilórica e da fúndica. Uma das vantagens dessa técnica é o diagnóstico de cepas predominantemente cocoides, que, nas colorações de rotina, são mais difíceis de serem observadas (McNulty et al, 2011).…”
Section: Resultsunclassified
“…e a ocorrência de úlceras gastroesofágicas em suínos tem sido controversa. Embora alguns autores (Szeredi et al, 2005;Proietti et al, 2010) tenham observado a relação entre a presença do Helicobacter spp. e a prevalência e a severidade das úlceras gástricas, outros não o fizeram (Ramis et al, 2007).…”
Section: Relataram Que Ounclassified
“…2A) (Muggenburg et al, 1964;O'Brien, 1993;Szeredi et al, 2005). A frequência de alterações histológicas na pars esophagea encontrada neste estudo e os resultados obtidos em outras investigações com análise macroscópica sugerem que essas lesões são muito frequentes no rebanho suíno brasileiro (Monticelli et al, 1995;Carvalho et al, 1999;Yamasaki et al, 2006 (Park et al, 2003) e que a patogenia das lesões gástricas está relacionada à espécie infectante.…”
Section: Resultsunclassified
“…Há relatos que demonstram associação positiva entre as lesões gástricas e Helicobacter spp. (Barbosa et al, 1995;Young et al, 2001;Mall et al, 2004) enquanto em outros essa relação é inconsistente (Melnichouk et al, 1999;Krakowka et al, 2005;Szeredi et al, 2005). Em cães, há um estudo recente de prevalência de helicobactérias e alterações na mucosa gástrica de animais saudáveis (Moutinho et al, 2007).…”
Section: Introductionunclassified